Exposure assessment and the risk associated with trihalomethanes compounds in drinking water - doi: 10.5020/18061230.2012.p5 - Aldo Pacheco Ferreira; Cynara de Lourdes Nóbrega da Cunha (Universidade de Fortaleza, 2012)
To measure the concentrations of trihalomethanes (THMs) in marshland of Jacarepaguá drinking water, Rio de Janeiro-RJ, Brazil, and their associated risks. Methods: Two hundred houses were visited and samples were collected from consumer taps water. Risks estimates based on exposures were projected by employing deterministic and probabilistic approaches. Results: The THMs (dibromochloromethane, bromoform, chloroform, and bromodichloromethane) ranged from 3.08 μg/l to 129.31 μg/l. Non-carcinogenic risks induced by ingestion of THMs were below the tolerable level (10 -6 ). Conclusion: Data obtained in this research demonstrate that exposure to drinking water contaminants and associated risks were higher than the acceptable level.